Promoting effects of NaCl and KCl stresses on astaxanthin yield in Microcystis flos-aquae - Junjie Ma; Zhehan Yang; Zhuxin Jin; Lexin Huang; Yinggang Wei; Wangbo Chen; Zhaojiang Zuo (Food Chemistry: X)
This study was to uncover the astaxanthin accumulation mechanism of Microcystis flos-aquae stressed by NaCl and KCl and select the optimal condition for astaxanthin production. Both of NaCl and KCl stresses showed inhibiting effects on M. flos-aquae growth by reducing photosynthetic abilities and causing reactive oxygen species accumulation. With raising the two salt concentrations, astaxanthin content and yield gradually increased, and the highest accumulation was under 300 mM for each salt, which should result from the up-regulation of 6 related genes promoting the precursor (β-carotene and zeaxanthin) transformation. KCl stress was more effective for improving astaxanthin yield than NaCl stress, which was strongly related with the salt concentration and astaxanthin content. Compared with other potential suitable conditions (35°C and purple light), 300 mM KCl also exhibited maximum effect on astaxanthin accumulation. Therefore, M. flos-aquae is first identified to synthesize astaxanthin, and KCl stress is more favorable to the compound production.